User-Driven Prosthetic Robotic Arm for Patients with Lower Arm Amputation - Hussin, Qazeem; Sadun, Amirul Syafiq (Progress in Engineering Application and Technology, 2021)
A very painful experience for a person would be the loss of a limb. Prosthetics Robotic Arm is a system that can help user recover some of the functions. Nevertheless, prosthetics can be very costly without insurance. As a result, there is a high demand for an effective yet low-cost prosthetics. The Prosthetic Robotic Arm is mentioned in various papers and researches. Since carrying out their study, developers were able to dramatically change their method to become more reliable and effective to match with today's market. The creation of a Prosthetic Robotic Arm through its electrical and mechanical architecture is addressed in this project. This project also uses an Arduino microcontroller to design a prosthetic that uses electromyographic sensor to detect signals from the residual limb and powers motors for movement. Future researchers can improve the prosthetic arm design to make it work more efficiently.